Incidence and risk factors for venous thromboembolism, bleeding, and death in colorectal cancer (Cancer‐VTE Registry). Issue 11 (11th September 2022) - Ikeda, Masataka; Uetake, Hiroyuki; Yoshino, Takayuki; Hata, Taishi; Oba, Mari S.; Takita, Atsushi; Kimura, Tetsuya
Abstract: The impact of venous thromboembolism in Japanese colorectal cancer patients has not been elucidated. This prespecified subanalysis of the Cancer‐VTE Registry aimed to report venous thromboembolism and event data after 1 year of follow‐up in 2477 patients with colorectal cancer and investigate risk factors of venous thromboembolism. Of 2477 patients, 158 (6.4%) had venous thromboembolism in venous thromboembolism screening at enrollment. Asymptomatic distal deep‐vein thrombosis accounted for 123/158 (77.8%) of venous thromboembolism cases. During the follow‐up period, symptomatic, incidental events requiring treatment and composite venous thromboembolism incidences were 0.3%, 0.8%, and 1.0%, respectively. The incidence of bleeding events, cerebral infarction/transient ischemic attack/systemic embolic event, and all‐cause death were 1.0%, 0.3%, and 4.8%, respectively. These results were consistent with the main study results. In multivariable analysis, venous thromboembolism at baseline was a risk factor of composite venous thromboembolism during the follow‐up period. Japanese patients with colorectal cancer and advancing cancer stage before treatment had more frequent venous thromboembolism complications at baseline, higher incidence of venous thromboembolism events during cancer treatment, and higher mortality. Abstract : As data on venous thromboembolism (VTE) in Japanese colorectal cancer patients are unclear, this pre‐specified sub‐analysis of the Cancer‐VTE Registry reported VTE and event data after 1‐year follow‐up in 2477 patients with colorectal cancer and investigated risk factors of VTE. Symptomatic, incidental events requiring treatment, and composite VTE incidences were 0.3%, 0.8%, and 1.0%, respectively, and the incidences of bleeding events, cerebral infarction/transient ischemic attack/systemic embolic event, and all‐cause death were1.0%, 0.3%, and 4.8%, respectively. VTE at baseline was a risk factor of composite VTE during the follow‐up period.